Synthesis and characterisation of mesoporous silicate nanoparticles for use as nanobiocatalysts - Bujedo, Agustín Anibal (2023)
Nano-biocatalysts are defined as those nanoparticles (NPs) that are capable of entrapping enzymes, transporting them and ultimately allowing catalysis to occur within the nanopores or releasing the enzyme in a controlled manner at the target site. NPs have the ability to interact with cells and tissues at the molecular level. It has been proposed that encapsulation in nanocarriers protects the bioactive components from unfavourable environmental conditions and also increases their solubility and bioavailability. We have synthesised mesoporous silicate nanoparticles using the method described by Nandiyanto et al1. It uses polystyrene as a template for the mesoporous structure and a surfactant and hydrocarbon solvent to control particle size. Different synthesis conditions were tested and the structural characteristics such as NP diameter and specific surface area (SSA) were analysed by SEM microscopy and dynamic vapour sorption, respectively. It was observed that NPs ranging from 52 to 98 nm were obtained and the SSA is compatible with mesoporous materials (194 m2 /g). Adsorption of the enzyme b-galactosidase from Kluyveromyces lactis was achieved at 48%. The chemical composition was analysed by EDS and mainly SO2 materials were observed.